Simplified expression is 11y² + 6x - 13
Step-by-step explanation:
- Step 1: Simplify 5y² + 3y - 13 + 6x - 3y + 6y²
5y² + 3y - 13 + 6x - 3y + 6y² = 11y² + 6x - 13
Answer:
f(6) = 1
Step-by-step explanation:
Function:
f(x) = -2/3x + 5
f(6) = -2/3(6) + 5
f(6) = -4 + 5
f(6) = 1
<span>growth whose rate becomes ever more rapid in proportion to the growing total number or size.
</span>
Answer:
10.2
Step-by-step explanation:
if u write is down with the decimals tgat and count that is what u would get also 2 plus 8 is ten and two pluse two is 41
Answer:
40%
Step-by-step explanation:
24/60 is 40%